KOMUNIKASI INTERPERSONAL KONSELOR DENGAN RESIDEN DALAM REHABILITASI NARKOBA DI YAYASAN SARASEHAN PEKANBARU - Muhammad Ramadhan Marmis; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Drug cases from year to year show a graph of an increase, this can damage the nation, drug rehabilitation in its own way can rehabilitate it, in many drug rehabilitation places, one of the rehabilitation places in Riau Province is the Pekanbaru Sarasehan Foundation. This study aims to find out how to communicate interpersonally between counselors and residents, how to empathize with counselors and residents, how to support counselors to residents, how to have positive attitudes from counselors to residents and how to act with residents in drug rehabilitation at the Pekanbaru Sarasehan Foundation. This study uses a descriptive approach, and uses Social Penetration Theory. The subjects in this study were counselors and residents of the Pekanbaru Sarasehan Foundation. The technique for determining research subjects was using the Purposive Technique. In this study, there were 6 informants. The data collection techniques used were interview, observation, and documentation techniques. In addition, the technique of checking the validity of the data uses the Triangulation Technique and the Participation Technique. These results indicate that counselors and residents at the Pekanbaru Sarasehan Foundation use five aspects of Interpersonal Communication at the time of Rehabilitation counseling, the first aspect is guiding, counselors are seen to do pleasantries before proceeding to therapeutic methods and make good reports at the beginning of the meeting, and it seems that residents feel comfortable and familiar so that they are more open, the second aspect is empathy, the counselor is able to understand the situation faced by the resident, and does not judge the resident badly, the third aspect is a positive attitude, the counselor gives an assessment, when giving feedback and attention to the resident, the fourth aspect is a supportive attitude, support, enthusiasm, and support for residents and provide emotional motivation, to fellow colleagues, counselors, seen together, residents assume that the counselor is asking his friends. Keywords: Interpersonal Communication, Counselor, Resident, Drug Rehabilitation.